Quantitative Descriptive Analysis of the Potential for Implementing Open and Distance Learning in Senior and Vocational High Schools - Mastur; Bunyamin Maftuh; Sarbaini; Encep Syarief Nurdin; Hamsi Mansur (JTP - Jurnal Teknologi Pendidikan, 2025)
quality gaps despite a Gross Enrollment Rate (GER) of 98.10%. Geographic barriers, economic constraints, and unequal teacher distribution underscore the need for alternative delivery models. This study assessed the potential implementation of Open Schooling and Distance Learning for senior and vocational high schools in South Kalimantan. Using a quantitative descriptive design, data were collected from principal and teacher questionnaires, facility observations at 30 Learning Activity Centers, and document review of GER, Net Enrollment Rate (NER), and the national Education Data System (Dapodik). Descriptive statistics (mean, percentage, and frequency) showed that major barriers were limited digital infrastructure, substandard teacher–student ratios, and weak local regulations. Nevertheless, 77% of teachers supported the open/PJJ model, and most schools demonstrated adequate information and communication technology (ICT) readiness, indicating high feasibility. The novelty of this study lies in combining stakeholder perceptions, school ICT readiness, and learning activity centers conditions to map provincial-level implementation feasibility. The findings provide evidence for provincial policymaking, particularly in developing regulations, strengthening ICT infrastructure, and expanding learning activity centers in remote areas to improve equity, reduce dropout rates, and support high-quality 12-year compulsory education.